The Innovative Household Solar Oven for Cooking - Fayziev P.R. (Genius Journals, 2022)
The test results of a new innovative solar household oven for cooking are given, the design features of the oven are indicated, the advantages are ease of use, reliability, wind resistance, transportability, and an absorber is used instead of mirrors to further increase the temperature inside the oven chamber.
Keywords: Solar oven; hot box; thermal insulation transportability; convenient operation